Praktik Cash Flow Management Mahasiswa dalam Penggunaan Pembayaran Digital - Nurul Chalisa Majiding (Jurnal Akuntansi Nommensen, 2026)
This study aims to understand students’ cash flow management practices in the use of digital payments. The focus is directed at how students manage income, allocate expenses, monitor balances, use transaction histories, and control spending through e-wallets, QRIS, mobile banking, and other digital payment instruments. This study employs a descriptive qualitative approach involving active undergraduate students from six universities in Makassar City. Informants were selected using purposive sampling based on the criterion of being active users of digital payments. Data were collected through in-depth interviews, limited documentation, and a simple financial diary. The simulated findings indicate that digital payments have become part of students’ financial habits, particularly for food, transportation, academic needs, online shopping, and peer-to-peer transfers. Students’ cash flow management practices remain simple, informal, and mostly reactive. Students control their spending by limiting e-wallet balances, checking transaction histories, and postponing non-priority purchases. However, repeated small transactions, promotions, cashback offers, social pressure, and easy top-ups often lead to cash flow leakage. This study emphasizes that digital payments can function as a financial control tool when supported by adequate digital financial literacy and self-control.